Tutorship among Equals: Historical Background and Psychopedagogical Principles - Sánchez Chacón, Giovanni (2014)
This article presents an overview of the historical background concerning literature, conceptualization and typology of peer tutoring and its implications for educational practices. Later reference to specific methodologies using peer tutoring is made, offering a recommendations for implementation in the classroom.